2018
DOI: 10.18178/ijiet.2018.8.5.1062
|View full text |Cite
|
Sign up to set email alerts
|

Using Mobile Apps to Support Effective Game-Based Learning in the Mathematics Classroom

Abstract: Abstract-Math is considered as the basis of the development of science, technology and thought. Traditional teaching methods emphasize on repeatedly exercising Math problems, which lead to a result that students lack understanding and thinking. Theming on elementary Math "Graphics and Space," this study has developed an interactive Math learning material (APP) through the ADDIE teaching design model. The content of this App contains units of Math "Volume", "Surface Area", "Bulk", "Area", "Perimeter." Each unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…This shows that the learning media developed are practical and can provide students' interest and motivation in the mathematics learning process compared to learning that has been implemented in schools, namely traditional methods. These results are in line with research conducted (Chao et al, 2018;Fabian et al, 2018;Qolbi, Thaariq, Az-Zahroh, Anwar, & Faiza, 2019;Widjayanti, Masfingatin, & Setyansah, 2019).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This shows that the learning media developed are practical and can provide students' interest and motivation in the mathematics learning process compared to learning that has been implemented in schools, namely traditional methods. These results are in line with research conducted (Chao et al, 2018;Fabian et al, 2018;Qolbi, Thaariq, Az-Zahroh, Anwar, & Faiza, 2019;Widjayanti, Masfingatin, & Setyansah, 2019).…”
supporting
confidence: 92%
“…Several important case studies related to the effects of using mobile tools and applications and online applications in mathematics learning at all levels of education can motivate students and get positive responses, making mathematics more fun and interactive than ordinary teaching practices or lectures or traditional methods (Drigas & Pappas, 2015;Fabian, Topping, & Barron, 2018;Skillen, 2015;Sung, Chang, & Liu, 2016;Vlachopoulos & Makri, 2017). M-learning can increase interest and motivation for parents and learners in learning mathematics and provides opportunities for various methods of teaching mathematics (Chao, Yang, Hsien, & Chang, 2018;Taleb, Ahmadi, & Musavi, 2015) Furthermore, the existence of an interactive mobile application enables students to have plenty of time and ways to practice problem-solving outside the classroom (Figueiredo, Godejord, & Rodrigues, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these, several studies have also pointed out that GBL, together with technology, can further support student learning in various areas (e.g., Behnamnia et al, 2022;Beşaltı & Kul, 2021;Bringula et al, 2018;Garcia, 2020;Godoy Jr., 2020). Other studies have also indicated that GBL with technology creates a positive effect on students as well as on achieving learning outcomes (Cahyana et al, 2017;Chao et al, 2018). Therefore, GBL applications for mathematics can be a fun and engaging way for students to learn and practice math skills and can be used in various educational settings, from the classroom to online learning environments.…”
Section: Game-based Learning For Mathematicsmentioning
confidence: 98%
“…Profesionalisme di sini mengacu pada sikap atau kondisi dalam menjalankan pekerjaan yang membutuhkan keahlian melalui pendidikan dan pelatihan tertentu, serta dilakukan sebagai sumber penghasilan. Selain itu, profesionalisme juga memiliki dampak yang signifikan terhadap produktivitas kerja (Chao, et al, 2018;Lakhan, et al, 2018;Usman & Yanti, 2020), salah satu kompetensi penting bagi seorang guru adalah kemampuan pedagogik, yang meliputi kemampuan merencanakan, melaksanakan pembelajaran, dan menilai hasil pembelajaran. Kemampuan ini sangat memengaruhi kualitas perencanaan dan pelaksanaan penilaian (Nurhayati & Rakhman, 2013).…”
Section: Pendahuluanunclassified